ANALISA PENGARUH PDRB, KREDIT MODAL KERJA, DAN UMP TERHADAP JUMLAH USAHA KECIL DAN MENENGAH (UKM) DI DAERAH ISTIMEWA YOGYAKARTA - Unggul Priyadi; Anjar Riyanto (Asian Journal of Innovation and Entrepreneurship, 2014)
This research uses secondary data as data sources. This research learnsthe effect ofregional gross domestic product, working capital loans, and province minimum wage towards SMEs developments in Daerah Istimewa Yogyakarta province. Models of analysis that used are analysis tools data panel (pooled data) as data processing tool which data panel is a combination  between time series (time-series data) from 2007 – 2011 and cross section (cross-section data) in five regencies in Daerah Istimewa Yogyakarta province. Statisticaltest uses three models those are common effect, fixed effect, random effect. The result of analysis data shows RGDP and working capital loans significantly take positive effect toward SMEs in Daerah Istimewa Yogyakarta province where RGDP grows higher followed by the econimic development so as SMEs grow higher nor working capital loans which released by commercial bank more bigger so as SMEs grow higher. Contrast with province minimum wage which is makes  significanly negative effect toward SMEs, which is possibility caused by the bigger province minimum wage becomes constraints toward cost ofproduction but conversely the smaller province minimum wage will push the development of SMEs in Yogyakarta. Keywords: SMEs, pooled data, fixed effect